2018
DOI: 10.1016/j.scitotenv.2017.08.248
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of N and P from waste water by using natural reactive hybrid sorbents: Nutrients (N,P,K) release evaluation in amended soils by dynamic experiments

Abstract: 13The removal of nutrients (nitrogen (N), phosphorous (P)) from waste water has become a resource 14 recovery option in recent regulations worldwide, as observed in the European Union. Although both 15 of these nutrients could be recovered from the sludge line, more than 70-75% of the N and P is 16 discharged into the water line. Efforts to improve the nutrient recovery ratios have focused on 17 developing low-cost technologies that use sorption processes. In this study, a natural zeolite 18 (clinoptilolite ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…However, comparison of plant uptake from sorbents with different sorption properties would be interesting. One other study has looked at desorption of nutrients from wastewater in soils without plants [26]. Here, it was found that the sorbent (clinoptilolites) released ammonium (and other ions) slowly over many watering cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparison of plant uptake from sorbents with different sorption properties would be interesting. One other study has looked at desorption of nutrients from wastewater in soils without plants [26]. Here, it was found that the sorbent (clinoptilolites) released ammonium (and other ions) slowly over many watering cycles.…”
Section: Discussionmentioning
confidence: 99%
“…One way to concentrate nutrients in wastewater and waste with high water content would be to sorb it to cheap and abundant sorbents before dewatering [5,6]. The sorbent loaded with nutrients can then be applied to agricultural soils as fertilizer [26]. However, there are few studies to characterize the availability of sorbed nutrients to support plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that ammonia sorbed as gas was bioavailable, but the degree of availability was not compared to conventional fertilizer application [55]. Another study found that sorbed nutrients were slowly desorbed in soil [56]. Our own unpublished studies suggest that ammonium sorbed to zeolite is less plant available than conventionally added ammonium.…”
Section: What Do We Know About How Treatment Options Affect Plant Avamentioning
confidence: 96%
“…Numerous studies and field applications of these minerals have been reported, providing environmental and technological solutions to the aforementioned industrial activities, including: i) the uptake of pollutants from wastewaters (Itskos et al, 2010;Moreno et al, 2001;Querol et al, 2006;Balsamo et al, 2012Balsamo et al, , 2010; ii) agriculture (Guaya et al, 2018;Gholamhoseini et al, 2013); iii) ecological restoration and soil amendments (Buondonno et al, 2013;Burger et al, 2011;Larney and Angers, 2012;Vallejo et al, 2012); and iv) organics waste composting (; Nissen et al, 2000;Villaseñor et al, 2011;Zorpas et al, 2000). Attention has also been paid to the synthesis of K-zeolites from fly ash and its potential applications have also been of interest and lead to a series of studies focused mainly on the synthesis of philipsite and chabazite for potential agriculture purposes (Amrhein et al, 1996;Murayama et al, 2008;Querol et al, 1997;Zeng et al, 2002) The interest on K-zeolites has been grown in the last years in view of its potential application in agriculture as slow release fertilizers.…”
Section: Introductionmentioning
confidence: 99%